THE INDONESIAN CONTEXT: THE MODERATING ROLE OF ENVIRONMENTAL UNCERTAINTY ON STRATEGIC CAPABILITIES AND SMES’ EXPORT PERFORMANCE INTERRELATIONSHIP (Lex localis - Journal of Local Self-Government, 2025)
This study examines whether environmental uncertainty has a moderating effect on the relationship between various strategic capabilities and the export performance of 174 Indonesian SMEs. The finding of this study indicates that all strategic capability factors have a significant effect on the export performance of SMEs. Environmental uncertainty, on the other hand, did not appear to have a significant moderating effect on interrelationships. Indonesian SMEs that have already expanded or are considering exporting can benefit from acquired knowledge regarding the critical factors to emphasise during the exporting process. Additionally, the government might place a greater emphasis on ways to facilitate the exporting process for SMEs.